NAMANYA JUGA PROYEK UJI COBA: Teknologi Kepengaturan dan Unintended Outcomes pada Aktivitas Demonstrasi REDD+ di Kalimantan Tengah - , Manggala Ismanto; , Dr. Pujo Semedi H.Y., MA. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
In this thesis I try to see how the connections between local and global entities occured, between the villagers of Petak Puti and demonstration activities (DA) of REDD +. Both of these entities met when the global discourse on climate change appear. Those entity eventually influenced and intertwined so as to produce what is arguably known as an unintended outcomes. To study the local aspect, I trace historically about how Petak Putiâs villagers Puti transformed. I use livelihood as an entrance to see how people adapt to their environment. Agrarian transformation ensued in this area, starting from the system of economic dualism (subsistence also with a cash crop) toward a single system of market-oriented in commercial crops. In addition, the community also has experience in dealing with governmentality interventions related to the management of forests and peatland, such as Mega Rice Project, CKPP, GNRHL, DAK DR and HTR which offers improvement for the environment and also population. and also presents some problems. Later in the global sphere I tried to trace the technology of governmentality in environment, in this case the governmentality of climate. I see how the journey of climate change discourse globally established, then producing regime and also the apparatus of interventions to overcome these problems. After that, REDD demonstration activity project was born as a response to global environmental governance regime in which third world countries become the main site to reduce global carbon emissions, which is actually produced by industrialized countries. When these two entities (Petak Puti People and KFCP) meet in the global agenda to mitigate climate change, emerging friction occurs due to a variety of interests in the Petak Puti village. The establishment of new institutions collide with the interests of the village governmentâs elite. Then, it turns out reforestation program lead to inequality among people from the incentives that offered. In addition, the potential for land conflicts likely to occur due to the effect of the presence of alternative livelihood programs which introduced rubber seeds.